2021
DOI: 10.1002/psp4.12736
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic modeling of GS‐441524, the active metabolite of remdesivir, in Japanese COVID‐19 patients with renal dysfunction

Abstract: Remdesivir, a prodrug of the nucleoside analog GS‐441524, plays a key role in the treatment of coronavirus disease 2019 (COVID‐19). However, owing to limited information on clinical trials and inexperienced clinical use, there is a lack of pharmacokinetic (PK) data in patients with COVID‐19 with special characteristics. In this study, we aimed to measure serum GS‐441524 concentrations and develop a population PK (PopPK) model. Remdesivir was administered at a 200 mg loading dose on the first day followed by 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
5
16
1
Order By: Relevance
“…Efforts to fit more complex models to the data resulted in parameter estimates with high residual errors, which could be a result of the limited sample size in this study. Nevertheless, the developed one-compartment model showed good resemblance between the predicted and measured concentrations of remdesivir and GS-441524 and is in line with the results of Sukeishi et al for GS-441524 ( 21 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Efforts to fit more complex models to the data resulted in parameter estimates with high residual errors, which could be a result of the limited sample size in this study. Nevertheless, the developed one-compartment model showed good resemblance between the predicted and measured concentrations of remdesivir and GS-441524 and is in line with the results of Sukeishi et al for GS-441524 ( 21 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, the lower elimination half-life could also be related to differences in study populations or study procedures. GS-441524 clearance in COVID-19 patients was higher than that previously reported (27.6 L/h versus 11.8 L/h), a possible result of the higher median eGFR, differences in ethnicity or the severity of disease, or the lack of remdesivir concentration data in the study population ( 21 ). The volume of distribution was larger for remdesivir and GS-441524 than that in healthy individuals, which can be explained by the high BMI of the patients in the study population or potentially disease- or treatment-related factors.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“… 26 The high volume of distribution of GS-441524 (6.36 L/kg) is consistent with this interpretation. 27 Upon comparison of differences in pharmacokinetic characteristics in plasma between humans and rats, despite different routes of drug administration, similar remdesivir and GS-441524 pharmacokinetics characteristics were observed. Remdesivir followed a rapid decline 28 and the absorption of GS-441524 appeared at the second time-point, with a slow elimination phase.…”
Section: Discussionmentioning
confidence: 91%
“… 11 Contrary to the precautionary advice, for patients with eGFR <30 some reported studies recommend dose adjustment rather than precautionary limits. 12 On the other hand, animal studies demonstrated potential, beneficial, renal effects in reversing obstructive renal fibrosis. 13 Of note, such cohort of patients with chronic kidney disease at significant risks of acquisition and complications of COVID‐19 disease as highlighted from multiple observational studies.…”
Section: Discussionmentioning
confidence: 99%